THE MOLECULAR MECHANISMS INVOLVED IN DOXORUBICIN-INDUCED SKELETAL MUSCLE WASTING - Moreira-Pais, Alexandra (2022)
Chemotherapeutic agents like doxorubicin (DOX) are the foundation for the treatment of a variety of malignancies; however, these therapies have several side-effects. DOX may trigger or potentiate the muscle wasting observed in cancer patients, which is particularly worrying in frail old patients. Therefore, it is important to comprehend the mechanisms responsible for DOX-induced toxicity in skeletal muscle, to identify therapeutic targets envisioning the improvement of survival rates and quality of life of these patients. Hence, this review discusses the molecular players that may be involved in DOX-induced muscle wasting. From the analysis performed herein, DOX seems to induce the activation of the proteolytic ubiquitin proteasome pathway (UPP), which in turn can also be enhanced by DOX-induced increase in myostatin and tumor necrosis factor (TNF)-α signaling pathways, as well as insulin resistance. Furthermore, DOX-induced oxidative stress and mitochondrial dysfunction may also be critical contributors for muscle wasting. All these mechanisms may contribute to the loss of skeletal muscle mass and function observed after DOX exposure, which may lead to or aggravate cachexia, responsible for more than 20% of all cancer-related deaths.